1991
DOI: 10.1111/j.1476-5381.1991.tb12182.x
|View full text |Cite
|
Sign up to set email alerts
|

The differential contribution of endogenous prostaglandins to the release of acetylcholine from the myenteric plexus of the guinea‐pig ileum

Abstract: 1 Prostaglandin E (PGE) may be essential for maintaining the sensitivity of the myenteric plexus of guinea-pig ileum to nicotine. The contributions of prostaglandins to nervous activity evoked by different stimuli have now been investigated by measuring the amount of acetylcholine (ACh) released from the myenteric plexus of the guinea-pig ileum. 2 The amount of ACh released in response to dimethylphenylpiperazinium (DMPP) or substance P was depressed to about 40% of control by 2.8 pM indomethacin (Ind), wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
33
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…The discrepancy between our finding and Capassso & Sorrentino's observation (1997) could be explained on the basis of a difference in the concentration of endogenous and exogenous arachidonic acid and also some other kinetic parameters (such as temperature). Although arachidonic acid at low concentration (10 mM) had a restorative effect on the electrical field stimulation-induced contraction of guinea-pig ileum which reduced by mepacrine (Takeuchi et al 1991), it appeared from the present data that arachidonic acid at high concentration (300 mM) not only did not potentiate withdrawal-induced contractures but also diminished their amplitude. In our previous study it was shown that arachidonic acid also reduced the response to acetylcholine but not to histamine (Mohammadi et al 1999).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…The discrepancy between our finding and Capassso & Sorrentino's observation (1997) could be explained on the basis of a difference in the concentration of endogenous and exogenous arachidonic acid and also some other kinetic parameters (such as temperature). Although arachidonic acid at low concentration (10 mM) had a restorative effect on the electrical field stimulation-induced contraction of guinea-pig ileum which reduced by mepacrine (Takeuchi et al 1991), it appeared from the present data that arachidonic acid at high concentration (300 mM) not only did not potentiate withdrawal-induced contractures but also diminished their amplitude. In our previous study it was shown that arachidonic acid also reduced the response to acetylcholine but not to histamine (Mohammadi et al 1999).…”
mentioning
confidence: 52%
“…Although the modulatory roles of endogenous arachidonic acid in the cholinergic system of various smooth muscles have previously been extensively investigated (Tamaoki et al 1987;Takeuchi et al 1991), only few reports have recently focussed on the role of arachidonic acid cascade in the modulation of opioidergic system (Capasso & Sorrentino 1997). With some evidence for induction of contractures in morphine withdrawal by endogenous arachidonic acid and inhibitory action of the exogenous arachidonic acid on Na π and Ca 2π conductances in neurones (Ordway et al 1991), it became of interest to verify whether exogenous arachidonic acid potentiates or attenuates the contractions of guinea-pig ileum elicited by naloxone after exposure to morphine.…”
mentioning
confidence: 99%
“…PGI2 and PGE2 reversed the inhibitory effects of IND on the ACh release (Takeuchi et al, 1991;Fukunaga et al, 1993). PGs were reported to increase cyclic AMP level in various tissues including the peripheral neuronal tissues (Harris et al, 1979;Kalix, 1979).…”
mentioning
confidence: 99%
“…Indomethacin (IND), an inhibitor of prostaglandin (PG) synthesis, inhibited nicotine and substance P-induced release of ACh from myenteric plexus of guinea pig ileum (Yagasaki et al, 1984;Takeuchi et al, 1991). PGI2 and PGE2 reversed the inhibitory effects of IND on the ACh release (Takeuchi et al, 1991;Fukunaga et al, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation